Associations between ectodermal dysplasia, psychological distress and quality of life in a group of adults with oligodontia. (17th November 2017) - Saltnes, Solfrid Sørgjerd; Jensen, Janicke Liaaen; Sæves, Rønnaug; Nordgarden, Hilde; Geirdal, Amy Østertun
Abstract: Objective: The aim of this study was to assess demographics, self-reported signs of ectodermal dysplasia (problems with hair, nails, skin and sweat glands), present teeth, previous dental treatment, psychological distress and QoL in individuals with oligodontia, and to explore the associations between these factors. We also aimed to compare the level of psychological distress and QoL between the study group and normative samples. Methods: Forty-seven individuals with oligodontia registered at a resource centre in Norway were included in the study. The participants completed self-administered questionnaires on demographics, ED signs, dental treatments, psychological distress and QoL (overall, health-related- and oral health-related QoL). Relevant statistics (independent t -test, correlation analysis and hierarchical multiple regressions) were used. Results: Thirty-five participants reported ED signs. Forty-one participants had tooth replacements (nine had removable dentures). Sixteen had ≤10 present teeth, 13 perceived dry mouth and seven were unemployed. Persons with ≤10 present teeth had higher anxiety- and depression-scores than those having >10 present teeth. Unemployment, dry mouth and removable dentures indicated poor health-related- and oral health related QoL. Compared to a normative sample; the study group had significantly poorer mental health (MH)-related QoL, mean (SD); (51.1(8.2) versus 46.8(9.3), p < .001) and more anxiety, mean (SD); (4.5(3.1) versus 6.7(3.6), p < .001). ED signs and treatments were most important for psychological distress and MH related QoL (MCS), whereas demographic parameters were most important for the other QoL measures. Conclusions: The psychological burden of oligodontia is significant, emphasizing the importance of a holistic approach by caregivers.